THE EFFECTS OF EDUCATION, TRAINING, AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE OF PRODUCTION DIVISION AT PT. X - Halipah, Kurnia Puspota; Pujianto, Surahman (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
This study aims to analyze and determine the effect of education, training, and career development on the performance of the Production Division employees at PT.X. The population used in this study were employees of the Production Division at PT. X as many as 113 employees. The sampling technique used is purposive sampling where the sampling technique with certain considerations is used as a sample, namely 67 permanent employees of the production division. The technique of collecting data is by distributing questionnaires using a Likert scale. The data were then analyzed using SPSS version 25. Based on the results of hypothesis testing data analysis in this study, it shows that education partially affects employee performance, training partially affects employee performance, and career development partially affects employee performance.